Contemporary Practice of Traditional Aboriginal Child Rearing: A Review - Muir, Nicole; Bohr, Yvonne (First Peoples Child & Family Review, 2014)
There is a dearth of literature available on traditional Aboriginal child rearing. This review paper explores Aboriginal child rearing to determine if traditional practices are still in use, how these may differ from mainstream child rearing and may have been modified by mainstream influences and colonialism. Traditional Aboriginal parenting is discussed in the context of colonialism and historic trauma, with a focus on child autonomy, extended family, fatherhood, attachment, developmental milestones, discipline, language, and ceremony and spirituality. This review was completed using the ancestral method i.e. using the reference list of articles to find other relevant articles and more structured literature searches. In light of the high number of Aboriginal children in foster care, this research may serve to highlight the role that historical issues and misinterpretation of traditional child rearing practices play in the apprehension of Aboriginal children. It may also assist non-Aboriginal professionals when working with Aboriginal children and their families.